Evaluating a Serious Game for Math: Is it Useful and Fun? - Diego Fellipe Tondorf; Marcelo da Silva Hounsell; Vanessa Andrade Pereira (Journal on Interactive Systems)
Background: Some arguing has been drawn in the literature questioning if a game can be purposeful (such as a Serious Game) and fun at the same time. Purpose: A serious game called Matemágica, designed to review basic mathematical operations and procedures, was selected to help delve in depth on this questioning. Methods: The evaluation assesses the game’s utility to teach mathematics and the fun perceived by its players. An empathic utility questionnaire was answered by 50 mature and experienced teachers, and a perceived fun questionnaire was created and answered by 334 students. Results: Girls and boys perceived similar fun and 3rd grade students (the actual target audience) felt just a little bit more fun than 4th and 5th grades. No significant difference was found between students from public and private schools. Overall, the game (Matemágica) was regarded as of high utility (scored 4.39 on a scale from 1 to 5) by the teachers and of high perception of fun (score 4,61 on a scale from 1 to 5) by the students. Conclusion: This paper shows that even a casual Serious Game can be useful and fun at the same time.